GURU MUGHNI KUNINGAN (1860-1935) - Helmi Hidayat (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2012)
There has been a strong linkage between the dissemination of Betawi culture and Islam in Jakarta. The prominent figures of Betawi are generally known as